Electronic properties of α-Mn-type non-centrosymmetric superconductor Re5.5Ta under hydrostatic pressure. (1st February 2023) - Mariappan, Sathiskumar; Bhoi, Dilip; Krishnan, Manikandan; Shoko, Nagasaki; Vajeeston, Ponniah; Arushi,; Kushwaha, Roshan Kumar; Singh, R P; Sonachalam, Arumugam; Uwatoko, Yoshiya
Abstract: We have studied the effect of hydrostatic pressure on the superconducting and normal state properties of the non-centrosymmetric superconductor Re5.5 Ta using magnetotransport, magnetization, and band structure studies. The superconducting transition temperature ( T c ) reveals a modest decrease of ∼0.52 K as the external pressure is raised to 8 GPa. We found the Maki parameter, α M > 1, both at ambient and high pressures, suggesting the significant role of the Pauli pair breaking effect. Furthermore, the lower critical field was found to decrease with a rate of −1.74 mT GPa −1 as pressure increases to 1.05 GPa. Analysis of the thermally activated flux flow region of ρ T, H using the Arrhenius equation reveals the coexistence of single and collective vortex states. Further analysis of the critical current density indicates that the surface and volume pinning centers coexist and remain unaffected with varying pressure. Band structure calculations were performed using density functional theory and reveal a large bulk modulus, B 0 ∼ 289 GPa with B 0 ′ ∼ 3.7, suggesting poor compressibility. In addition, we found that the density of states at the Fermi level barely reduces, even at pressures of up to 20 GPa. This is consistent with the experimental observation of robust superconductivity under compression.